Pengaruh Kualitas Informasi, Persepsi Keamanan, dan Persepsi Privasi Terhadap Kepercayaan Pengguna Belanja Online (Literature Review) - Elsa Pebiyanti; Achmad Fauzi; Tsamara Husniyyah; Sarah Intan Tasia; Zhakila Sutendi; Anisa Elsa Vitri (Dinasti Review, 2023)
This research was made aiming to examine the importance of the relationship between the three aspects above, namely information quality, perceived security and privacy for consumers in purchasing decisions for online shopping. This journal is written by applying quantitative writing methods and literature studies. The results showed that information quality, perceived security and privacy positively affect online shopping purchase decisions. In addition, discipline has a significant positive effect on employee performance. In the context of achieving one of the goals of marketing initiatives is customer satisfaction. To develop long-term client relationships with service providers, satisfaction alone may not be enough. Additional factors, including trust, are needed as important accelerators, especially when it comes to the development of online commercial partnerships. In addition, compared to transactions made at physical businesses, customers often lack confidence in their security and privacy when connected over the internet.